2D-layered inorganic nanomaterials (2D-LIN) for adsorptive mitigation of heavy metals: a next-generation contender for purification of textile effluent - Nag, Somrita; Das, Riyanka; Pal, Rajeshwari; Mondal, Moumita; Banerjee, Priyabrata (Springer, 2025)
The textile industry, despite being a cornerstone of global manufacturing and a major contributor to economic growth, is a leading source of environmental pollution, especially via effluents containing toxic heavy metals such as Pb2⁺, Cd2⁺, Cu2⁺, and Cr⁶⁺. These contaminants pose serious ecological and health threats due to their non-biodegradable and bio-accumulative nature. While conventional physical, chemical, and biological methods have been employed for wastewater treatment, adsorption has emerged as the most promising due to its operational simplicity, cost-effectiveness, and high removal efficiency under diverse environmental conditions. In this context, two-dimensional layered inorganic nanomaterials (2D-LINs) have garnered significant attention as next-generation adsorbents. Their exceptional properties, such as high surface area, tunable surface chemistry, and hydrophilicity, enable efficient capture of heavy metals even under adverse conditions. However, despite growing interest, research on the practical application of 2D-LINs for textile effluent treatment remains fragmented and underdeveloped. This review comprehensively consolidates recent advances in the development and application of 2D-LINs, including transition metal dichalcogenides (TMDs), transition metal carbides (MXenes), transition metal oxides (TMOs), and other variants such as LDH, h-BN, g-C₃N₄, and graphene oxide for the adsorptive removal of heavy metals from textile wastewater. Mechanistic insights into adsorption, material-specific performance metrics, kinetic and isotherm behaviours, and recyclability are critically analysed. The review also identifies key bottlenecks, such as pH sensitivity, regeneration limitations, and scalability challenges, and provides strategic recommendations for designing field-viable, surface-functionalized 2D-LIN architectures. By bridging current research gaps and highlighting future directions, this review aims to guide material scientists and environmental engineers toward the rational development of efficient and sustainable heavy metal mitigation technologies tailored to the textile industry.